Algebra and trigonometry with analytic geometry - Swokowski, Earl W. (Boston : PWS.KENT publishing company, 1981)
This text introduces trigonometric functions using the right triangle. This edition, with its improved design, is now more accessible. The emphasis is placed on graphical interpretation of information and the text now includes integrated calculator exercises
Include index.
Keywords: Algebra; Trigonometry; Geometry, Analytic